Endocrine outcomes after limited surgery and conformal photon radiation therapy for pediatric craniopharyngioma: Long-term results from the RT1 protocol. Issue 12 (27th April 2022) - Merchant, Thomas E; Edmonston, Drucilla Y; Wu, Shengjie; Li, Yimei; Boop, Frederick A; Lustig, Robert H
Abstract: Background: To estimate the incidence of endocrinopathy in children and adolescents with craniopharyngioma after treatment with photon-based conformal and intensity-modulated radiation therapy (CRT). Methods: One hundred one pediatric patients were enrolled on a phase II single-institution protocol beginning in 1998 (n = 76) or followed a similar non-protocol treatment plan (n = 25). Surgery was individualized. CRT (54 Gy) was administered using a 1.0-cm or ≤0.5-cm clinical target volume margin. Patients underwent baseline and serial evaluation of the hypothalamic-pituitary axis. Results: The 10-year cumulative incidence (CI) of growth hormone deficiency (GHD) was 68.42% (±11.27) for black patients and 94.23% (±3.57) for white patients ( P  = .0286). The CI of thyroid-stimulating hormone deficiency (TSHD) was 70.94% (±8.44) at 10 years for non-shunted patients and 91.67% (±10.40) at 6 years for shunted patients ( P  = .0260). The CI of TSHD was 100% (±14.29) at 4 years for those with diabetes insipidus (DI) and 71.36% (±8.86) at 10 years for those without DI ( P  = .0008). The 10-year CI of adrenocortical hormone deficiency was 70.00% (±16.15) for those with DI and 48.39% (±9.19) for those without DI ( P  = .0080). The 10-year CI of LH/FSH deficiency was 43.33% (±9.32) age <7 years, 61.29% (±9.11) aged 7-10 years, and 78.95% (±6.38) age ≥10 years ( P  < .0001). BMI was significantly greater prior to CRT in white patients with DI ( P  = .0004) and preexisting GHD ( P  = .0275). Conclusions: Hormone deficiencies are common in pediatric patients with craniopharyngioma and are associated with host, tumor, and treatment factors. Understanding the incidence and time to onset may facilitate intervention and patient selection for treatment.